The application of strand invasion phenomenon, directed by peptide nucleic acid (PNA) and single‐stranded DNA binding protein (SSB) for the recognition of specific sequences of human endogenous retroviral HERV‐W family. Issue 5 (6th December 2016) - Machnik, Grzegorz; Bułdak, Łukasz; Ruczyński, Jarosław; Gąsior, Tomasz; Huzarska, Małgorzata; Belowski, Dariusz; Alenowicz, Magdalena; Mucha, Piotr; Rekowski, Piotr; Okopień, Bogusław
Abstract: The HERV‐W family of human endogenous retroviruses represents a group of numerous sequences that show close similarity in genetic composition. It has been documented that some members of HERV‐W–derived expression products are supposed to play significant role in humans' pathology, such as multiple sclerosis or schizophrenia. Other members of the family are necessary to orchestrate physiological processes (eg, ERVWE1 coding syncytin‐1 that is engaged in syncytiotrophoblast formation). Therefore, an assay that would allow the recognition of particular form of HERV‐W members is highly desirable. A peptide nucleic acid (PNA)–mediated technique for the discrimination between multiple sclerosis‐associated retrovirus and ERVWE1 sequence has been developed. The assay uses a PNA probe that, being fully complementary to the ERVWE1 but not to multiple sclerosis‐associated retrovirus (MSRV) template, shows high selective potential. Single‐stranded DNA binding protein facilitates the PNA‐mediated, sequence‐specific formation of strand invasion complex and, consequently, local DNA unwinding. The target DNA may be then excluded from further analysis in any downstream process such as single‐stranded DNA‐specific exonuclease action. Finally, the reaction conditions have been optimized, and several PNA probes that are targeted toward distinct loci along whole HERV‐W env sequences have been evaluated. We believe that PNA/single‐stranded DNA binding protein–based application has the potential to selectively discriminate particular HERV‐W molecules as they are at least suspected to play pathogenic role in a broad range of medical conditions, from psycho‐neurologic disorders (multiple sclerosis and schizophrenia) and cancers (breast cancer) to that of an auto‐immunologic background (psoriasis and lupus erythematosus). Abstract : A peptide nucleic acid (PNA)‐mediated technique for the discrimination between multiple sclerosis‐associated retrovirus and ERVWE1 sequence has been developed. The assay uses a PNA probe that shows high selective potential. Single‐stranded DNA binding protein (SSB) facilitates the PNA‐mediated, sequence‐specific formation of strand invasion complex. This PNA/single‐stranded DNA binding protein‐based application has the potential to selectively discriminate particular HERV‐W molecules as they are at least suspected to play pathogenic role in several medical conditions.